2020
DOI: 10.21203/rs.3.rs-55924/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of task-specific virtual reality training using a Leap Motion Controller on hemiparetic upper extremity in patients with stroke

Abstract: Background: Task-specific training has been proven to be effective in promoting recovery of the hemiparetic upper extremities after a stroke. This study was to develop a new and innovative task-specific VR (TS-VR) program using a Leap Motion Controller VR device and the Unity3D program for distal hand function training, and to investigate whether a two-week program of TS-VR training would promote recovery of the hemiparetic upper extremity in patients with chronic stroke.Methods: We designed the TS-VR program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…In a study conducted with Leap Motion Controller (LMC, Leap Motion, Inc., San Francisco, CA, USA) by implementing the box and block test (BBT), an OT tool that evaluates hand motor ability in VR, it was confirmed that the conventional BBT and system BBT in a virtual space showed similar performance results, and the objective analysis was possible based on the data collected by tracking the real-time movement [19]. VR helps the user focus on virtual space by eliminating distractions in their surroundings and leaving only the performance environment [23]. This removes spatial constraints so that users can perform in any space and increase their immersion, and good results can be expected in terms of performance.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In a study conducted with Leap Motion Controller (LMC, Leap Motion, Inc., San Francisco, CA, USA) by implementing the box and block test (BBT), an OT tool that evaluates hand motor ability in VR, it was confirmed that the conventional BBT and system BBT in a virtual space showed similar performance results, and the objective analysis was possible based on the data collected by tracking the real-time movement [19]. VR helps the user focus on virtual space by eliminating distractions in their surroundings and leaving only the performance environment [23]. This removes spatial constraints so that users can perform in any space and increase their immersion, and good results can be expected in terms of performance.…”
Section: Introductionmentioning
confidence: 80%
“…Unity3D is a game engine that provides an intuitive graphical user interface (GUI) and a development environment of 2D and 3D [23]. Currently, it is actively used in various fields such as 3D animation, VR, and augmented reality (AR).…”
Section: D Modeling Of Gf Models and Implementation Of Virtual Spacementioning
confidence: 99%